Does centralization affect the number and size of lobbies? - Michela Redoano (Center for Economic Studies and ifo Institute (CESifo), 2007)
Previous research has shown that if countries merge, (i.e. move to centralized policy choices) the effect is to reduce lobbying. However empirical evidence suggests that this is not always the case. This paper attempts to explain the empirical evidence in a two-jurisdiction political economy model of endogenous lobby formation and policy determination. We measure lobbying in two ways: (i) the number of lobbies formed under the two settings and, (ii) their impact on policy decisions. We show that preference heterogeneity and lobby formation are positively related and that moving from decentralization to centralization can affect both the number and the type of lobbies. Under decentralization, if lobbies form they will always have an effect on policy decision. Under centralization, if lobbies form, lobby competition may completely offset their influence on policy; however it is possible that the threat of lobbying may affect policy even when no lobby forms in equilibrium. Finally, when lobbying affects policy (even if no lobby forms in equilibrium), the political equilibrium is always more moderate than the one where lobbying is not taken into account.
Keywords: H23; H77; D72; 330; Dezentralisierung; Zentrale Wirtschaftsplanung; Interessenpolitik; Interessenvertretung; Theorie